Improving Renewable Energy Transition Acceptance: A Simulation Gaming Approach on a Multi Actor Setting in the Netherlands - Sutrisno, Aziiz; Vennix, Jac A. M.; Syaifudin, Noor (Makara Journal of Technology, 2015)
The Netherlands have tried very hard to increase their renewable energy sources (RES) shares to fulfill the European Union target in 2050. However, RES performance did not show the expected result as the performance declined in 2009 producing even wider gap compare to the target. The Dutch government’s tried to incorporate all interested stakeholders by forming the Dutch energy transition task force. Nevertheless, the task force’s result is also not showing a desirable trend. Key reasons behind the Dutch low RES performance are the lack of shared understanding and positive attitude toward RES development among interested actors. This research uses a role-playing game to increase shared understanding and positive attitude within the actors. The game set players in a competing role as the government, an energy company and the end user. Players were given the ability to make decisions on their respective area. A pilot study was then conducted to measure the effectiveness of the game. The pilot study showed the game increased actor’s individual understanding and shared understanding. Moreover, it also showed that the game increases actor’s positive attitude toward RES development in the Netherlands.